Edukasi Peternak Budidaya Maggot Sebagai Bahan Pakan Sumber Protein di Kabupaten Sidenreng Rappang (Program Bina Desa Mahasiswa Fakultas Vokasi Univeristas Hasanuddin) - Yamin, Abdul Alim; Purwanti, Sri; Zulkharnaim, Zulkharnaim; Hasrin, Hasrin; Latief, M. Fadhlirrahman; Syamsu, Jasmal Ahmari (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The implementation of community service through the Students Village Empowerment Program aims to disseminate and educate on the cultivation and processing of maggot as a protein source for poultry and increase the knowledge of farmers in using maggot as an alternative feed in poultry rations. The benefits of community service activities were to provide skills and knowledge about maggot utilization as a source of poultry feed so that it can be applied in poultry feed by the target audience or farmers. The village empowerment activity of the students was carried out in Kanie Village, Maritengngae District, Sidenreng Rappang Regency. The object of farmer groups were native chicken farmers, domestic chicken traders, and layer chicken farmers who were the part of Prima Karya Sentosa Livestock Farmer Group (35 people). The stages of implementing the activity are preparation including coordination, team and participants preparation including the 25-student engagement of the Animal Production Technology study program (DIV), and preparation of extension materials. The extension method was carried out in the form of a lecture and discussion with all members of the group. Training infrastructure and other facilities were provided by the farmer group partner. All the participants were expected to have knowledge and skills in cultivating maggots including the BSF maggot life cycle, maggot nutrient content, and maggot application in the feed after attending the training. Therefore, assistance should be conducted for the sustainable program of poultry management, especially applying maggots as poultry feed ingredients.